2019
DOI: 10.3390/membranes9120167
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Carbonic Anhydrase on CO2 Separation Performance of Thin Poly(amidoamine) Dendrimer/Poly(ethylene glycol) Hybrid Membranes

Abstract: The effect of carbonic anhydrase (CA) on the separation performance of thin poly(amidoamine) (PAMAM) dendrimer/poly(ethylene glycol) (PEG) hybrid membranes was investigated. CA, a type of enzyme, was used to promote CO2 hydration and dehydration reactions and to assess whether these reactions were the rate-limiting step in CO2 permeation through the membrane. The relationship between the membrane thickness and the CO2 permeance was evaluated in CO2/H2 or CO2/He separation using PAMAM/PEG hybrid membranes (thic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…The target system in the present study was CO 2 /H 2 produced from the water‐gas shift reaction. To ensure safety, He was used instead of H 2 as in the past experiments 25,26 . The relationship between the permeances of He and H 2 is as follows: Q He ≈ 0.8 Q H₂ .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The target system in the present study was CO 2 /H 2 produced from the water‐gas shift reaction. To ensure safety, He was used instead of H 2 as in the past experiments 25,26 . The relationship between the permeances of He and H 2 is as follows: Q He ≈ 0.8 Q H₂ .…”
Section: Methodsmentioning
confidence: 99%
“…The relationship between the permeances of He and H 2 is as follows: Q He ≈ 0.8 Q H₂ . The permeance of CO 2 ; however, was almost the same for both CO 2 /He and CO 2 /H 2 separation 26 . The prepared membrane was first set in a cell for evaluation, and in the heating furnace, the cell and a stainless pipe were connected.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have confirmed that the separation performance is improved when either carbonate or amine‐based additives are included in the membrane 12,25–34 . Carbonate and amine moieties, which function as CO 2 carriers, require water to enhance their chemical reaction with CO 2 25,35,36 .…”
Section: Introductionmentioning
confidence: 93%
“…[20][21][22][23][24] Previous studies have confirmed that the separation performance is improved when either carbonate or amine-based additives are included in the membrane. 12,[25][26][27][28][29][30][31][32][33][34] Carbonate and amine moieties, which function as CO 2 carriers, require water to enhance their chemical reaction with CO 2 . 25,35,36 Among the alkyl carbonates, cesium carbonate is most frequently used as an additive for the CO 2 separation membrane.…”
Section: Introductionmentioning
confidence: 99%